Simmering Innards: Does Irritable Bowl Syndrome Have an Immunological Basis? - Christopher N Andrews; Eldon A Shaffer (Canadian Journal of Gastroenterology)
Not so long ago, physicians construed the irritable bowel syndrome (IBS) as being a neurotic trait: it was all in the head. Today most clinicians believe that the main abnormality lies in the brain (and spinal cord), which reacts abnormally to stimuli from the gut. Recent studies are identifying a basis for these neural changes - low grade inflammation in the gut - which may play a key role in IBS.